Methane-derived electrochemical sensor for determination of paracetamol and diquat - S. de Sá, Bruna [UNESP]; S. Stefano, Jéssica; G. e Silva, Luiz Ricardo; M. Perfecto, Tarcísio; Mazon, Talita; Volanti, Diogo P. [UNESP]; C. Janegitz, Bruno; Ribeiro, Caue (Elsevier, 2024)
Carbon materials are widely used as electrodes because their versatility allows the manufacture of different electrochemical sensors. Chemical vapor deposition (CVD) is a versatile route for their production, allowing carbon growth on different substrates, such as ceramic fiber paper (CFP), a flexible and easy-to-handle material composed of alumina, silica, inorganic binders, and organic residues. Here, we demonstrate a route for carbon electrode preparation over CFP using methane as an additional carbon source to improve the electronic properties of the material. Different synthesis temperatures were tested, and the sample produced at 1000 °C (CFP-1000) was electrically conductive. The new material was applied as an electrochemical sensor to determine paracetamol in drugs, tap water, and synthetic urine samples using differential pulse voltammetry (DPV) and diquat in tap water and wild honey samples by the square-wave voltammetry (SWV) technique. For both, it was observed that the matrix effects were insignificant for the sensor. The limit of detection (LOD) calculated for paracetamol was 0.05 μmol L−1, while the LOD for diquat was 0.001 μmol L−1.
Keywords: Carbon; Ceramic fiber paper; CVD method; Diquat sensor; Paracetamol sensor